Ruth Martínez Alcorlo, Isabel de Castilla y Aragón. Princesa y reina de Portugal (1470-1498), Madrid, Silex, 2021, 293 páginas, ISBN 978-84-18388-09-5 - Gómez, Lucía Belén (2021)
Fil: Gómez, Lucía Belén. Pontificia Universidad Católica Argentina; Argentina